Goldratt's rules of flow - Goldratt-Ashlag, Efrat (HighBridge, 2023)
Marc Wilson is not giving up. He is determined to turn around the struggling family company and keep it, despite his father's decision to sell. The problem is that they are late on more and more projects and their customers won't tolerate it anymore. Marc is looking everywhere for a solution, when in one of his MBA classes he comes across a unique approach that views operations in terms of flow. The concept of flow is straightforward. It's easy to visualize the stream of projects going through the system and understand that if something clogs the flow, the projects pile up; the lead time gets longer, and as a result the reliability of due dates suffers. What is not so easy is to uncover the specific obstacles that obstruct the flow and figure out how to remove them. Whether you're a manager in engineering, IT, service, or sales, this book will help you gain much better predictability and significantly improve your delivery.